1H-NMR study of some new acetyl dimethylbiphenyls: unambiguous signal assignment for the methyl groups. Issue 2 (1997) - Kamounah Kamounah, Fadhil S. Fadhil S.; Titinchi Titinchi, Salam J. Salam J.
Abstract : The abundance 1 H-NMR spectra of some new mono- and diacetyl compounds derived from 2, 2′-dimethyl-, 3, 3′-dimethyl-, and 4, 4′-dimethylbiphenyls were recorded. Unambiguous signal assignment of the methyl groups of the aromatic biphenyl rings were made for the structure elucidation.